2018
DOI: 10.3892/ijmm.2018.3654
|View full text |Cite
|
Sign up to set email alerts
|

Anti‑cancer effects of fisetin on mammary carcinoma cells via regulation of the PI3K/Akt/mTOR pathway: In�vitro and in�vivo studies

Abstract: Fisetin, a natural flavonoid found in a variety of edible and medical plants, has been suggested to inhibit the proliferation of various tumor cells and to induce apoptosis. However, the effects of fisetin on breast cancer have rarely been reported and the underlying mechanism is still undefined. The present study explored the anti-cancer effects of fisetin on mammary carcinoma cells and the underlying mechanisms. Following treatment with fisetin, viability of 4T1, MCF-7 and MDA-MB-231 cells were measured by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 51 publications
2
49
0
Order By: Relevance
“…The cellular AKT/mTOR axis plays an important role in cellular physiology and homeostasis [ 26 ]. Many small molecular drugs target this axis and contribute to control the tumor growth [ 27 ]. Autophagy is initiated in response to cellular stress, including Salmonella infection.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular AKT/mTOR axis plays an important role in cellular physiology and homeostasis [ 26 ]. Many small molecular drugs target this axis and contribute to control the tumor growth [ 27 ]. Autophagy is initiated in response to cellular stress, including Salmonella infection.…”
Section: Discussionmentioning
confidence: 99%
“…It was found in some vegetables and fruits such as lettuce, cucumbers, strawberry, and grapes (Sak et al, 2016). Previous studies have shown that FST has anti-tumor (Ferreira de Oliveira et al, 2018;Sun et al, 2018), anti-oxidation (Singh et al, 2018;Zhang et al, 2018), antiinflammatory Huang et al, 2018), and other pharmacological effects. It has been reported that FST inhibits inflammation related cytokines like TNF-a, IL-6, and NF-kB in streptozotocin (STZ)-induced diabetic cardiomyopathy rats (Althunibat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids can downregulate HIFα and VEGF in different cancer cell lines such as OVCAR-3, A2780, MCF-7 and PC-3 [ 42 , 70 , 95 , 131 , 144 , 145 ]. Many studies have also reported the ability of the flavonoids 3-hydroxy flavone, hesperidin, apigenin, fisetin and many others to reduce tumor size, capillary density and metastasis of different cancers, such as osteosarcoma, melanoma, lung and breast cancers, in xenograft mice [ 26 , 183 , 184 , 185 , 186 , 187 ].…”
Section: Discussionmentioning
confidence: 99%